Carbon emission from urban passenger transportation in Beijing. (December 2015) - Wang, Zijia; Chen, Feng; Fujiyama, Taku
Highlights: A method to estimate carbon emissions from all modes of urban passenger transport is established. Emissions from electricity consumed in transport should be calculated. Carbon emissions of Beijing's passenger transport increase fast in the last decade. Cars contribute much to emissions and shifting trips from cars to public transit is efficient for emission reduction. Abstract: Urban passenger transport significantly contributes to global greenhouse gas emissions, especially in developing countries owing to the rapid motorization, thus making it an important target for carbon reduction. This article established a method to estimate and analyze carbon emission from urban passenger transport including cars, rail transit, taxis and buses. The scope of research was defined based on car registration area, transport types and modes, the stages of rail transit energy consumption. The data availability and gathering were fully illustrated. A city level emission model for the aforementioned four modes of passenger transport was formulated, and parameters including emission factor of electricity and fuel efficiency were tailored according to local situations such as energy structure and field survey. The results reveal that the emission from Beijing's urban passenger transport in 2012 stood at 15 million tonnes of CO2, of which 75.5% was from cars, whereas car trip sharing constitutes only 42.5% of the total residential trips. Bus travel, yielding 28.6 g CO2, is the most efficient mode of transport under the current situations in terms of per passenger kilometer (PKM) emission, whereas car or taxi trips emit more than 5 times that of bus trips. Although a decrease trend appears, Beijing still has potential for further carbon reduction in passenger transport field in contrast to other cities in developed countries. Development of rail transit and further limitation on cars could assist in reducing 4.39 million tonnes CO2 emission.